(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
A -partite hypergraph is a hypergraph whose vertices can be partitioned into different independent sets. In this paper, operations on intuitionistic fuzzy -partite hypergraph(IF-PHG) are discussed and some properties were derived. The operations like union, intersection, join, structural subtraction, ringsum, product, cartesian product, composition and complement were discussed.